Genetic alterations in glucocorticoid signaling pathway components are associated with adverse prognosis in children with relapsed ETV6/RUNX1-positive acute lymphoblastic leukemia. Issue 5 (3rd May 2016) - Grausenburger, Reinhard; Bastelberger, Stephan; Eckert, Cornelia; Kauer, Maximilian; Stanulla, Martin; Frech, Christian; Bauer, Eva; Stoiber, Dagmar; von Stackelberg, Arend; Attarbaschi, Andishe; Haas, Oskar A.; Panzer-Grümayer, Renate
Abstract: The ETV6/RUNX1 gene fusion defines the largest genetic subgroup of childhood ALL with overall rapid treatment response. However, up to 15% of cases relapse. Because an impaired glucocorticoid pathway is implicated in disease recurrence we studied the impact of genetic alterations by SNP array analysis in 31 relapsed cases. In 58% of samples, we found deletions in various glucocorticoid signaling pathway-associated genes, but only NR3C1 and ETV6 deletions prevailed in minimal residual disease poor responding and subsequently relapsing cases ( p < 0.05). To prove the necessity of a functional glucocorticoid receptor, we reconstituted wild-type NR3C1 expression in mutant, glucocorticoid-resistant REH cells and studied the glucocorticoid response in vitro and in a xenograft mouse model. While these results prove that glucocorticoid receptor defects are crucial for glucocorticoid resistance in an experimental setting, they do not address the essential clinical situation where glucocorticoid resistance at relapse is rather part of a global drug resistance.